A Novel Analytical Method to Calculate the Amounts of Free and Adsorbed Gas in Shale Gas Production. (20th June 2018) - Li, Qingyu; Li, Peichao; Pang, Wei; Bi, Quanfu; Du, Zonghe; Li, Xuebin; Lu, Detang
Abstract : Shale gas has now become an important part of unconventional hydrocarbon resources all around the world. The typical properties of shale gas are that both adsorbed gas and free gas play important roles in gas production. Thus the contributions of free and adsorbed gas to the shale gas production have become a hot, significant, and challenging problem in petroleum engineering. This paper presents a new analytical method to calculate the amounts of free and adsorbed gas in the process of shale gas extraction. First, the expressions of the amounts of adsorbed gas, matrix free gas, and fracture free gas in shale versus the producing time are presented on the basis of Langmuir adsorption model and formation pressure distribution. Next, the mathematical model of multifractured horizontal wells in shale gas reservoirs is established and solved by use of Laplace transform and inversion to obtain the normalized formation pressure distribution. Finally, field case studies of two multifractured horizontal shale gas wells in China are carried out with the presented quantitative method. The amounts of adsorbed and free gas in production are calculated, and the adsorbed-to-total ratio is provided. The results show that the proposed method is reliable and efficient.